Organizational, economic and marketing aspects of creating a web as a tool for the development of a real estate agency - Mala, Iryna; Мала, Ірина Борисівна (Scientific Center of Innovative Researches OÜ, 2024)
In an era where digital transformation permeates every aspect of society, the Internet has become a cornerstone for both individuals and businesses. Today, practically every sector utilizes online resources to some extent, from streamlining operations to expanding market reach. This digital shift is especially pertinent for real estate agencies, where web resources are invaluable for connecting with potential clients. As the Internet becomes the go-to medium for property searches, the role of a well-designed, functional website has evolved from a luxury to an essential asset in the real estate market, especially within Ukraine’s dynamic housing landscape. For real estate firms, the creation and maintenance of a web presence are crucial, offering a streamlined way for clients to search properties, access up-to-date information, and make informed decisions with minimal effort.
Keywords: internet marketing; website promotion; real estate agency development tools